The Degradation Rates of Natural Dyes from Natural Resources: A Review - Armalina, Yesi; Azizah, Zikra; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: Natural plants can produce natural dyes. These dyes are widely used in the pharmaceutical and food fields, such as betacyanin, anthocyanin, carotenoids, flavonoids and others. Several external factors could cause natural dyes to show instability or degradation, some of the external factors are temperature, pH, storage time and so forth. Research on various kinds of natural dyes shows the degradation of these natural dyes. Degradation can cause damage to these plants dyes, therefore steps are needed to prevent the degradation of these dyes. The measurement of degradation was carried out to prevent the deterioration of natural dyes from natural materials that will be used or consumed. The purpose of this review is to determine the rate of degradation of natural dyes sourced from nature in accordance with the results of the studies that have been conducted. Data Sources Study Selection: Data sources of this review article taken from web Google Scholar, Science Direct, National Center for Biotechnology Information (NCBI), Scopus, and Pubmed. Conclusion: Natural dyes can be used for manufacture of food or drinks, natural dyes from plants instability due to degradation. Degradation occur because temperature, pH, storage time and sunlight.